Inclusions and subtypes - Martí-Oliet, Narciso; Meseguer, José (Computer Science Laboratory <Menlo Park, Calif.>: SRI-CSL, 1990)
Abstract: "The failure to make explicit two different notions of subtype, a subtype as inclusion notion originally proposed by Goguen [18] and a subtype as implicit conversion notion originally proposed by Reynolds [44], leads to unsatisfactory situations in present approaches to subtyping. We argue that choosing either notion at the expense of the other would be mistaken and limiting, and propose a framework in which two subtype relations [tau less than or equal to tau prime] (inclusion) and [tau less than or equal to]: [tau prime] (implicit conversion) are distinguished and integrated